Implementasi Program Pemberdayaan UMKM di Dinas Koperasi Usaha Kecil dan Menengah Kabupaten Minahasa - Tamboto, Angela; Sendouw, Recky H. E.; Mantiri, Jeane (CV. Kurnia Grup, 2024)
This study aims to investigate the implementation of UMKM empowerment programs at the Small and Medium Enterprises Agency of Minahasa Regency. The method used in this research is qualitative, employing data collection techniques such as interviews, documentation, and observation. The research focuses on program objectives and the effectiveness of UMKM empowerment program administration. The study was conducted at the Small and Medium Enterprises Agency of Minahasa Regency. The research findings regarding the Implementation of UMKM Empowerment Program at the Small and Medium Enterprises Agency of Minahasa Regency indicate that : 1) Program administration targets have not achieved the set targets and objectives. 2) The implementation of UMKM empowerment programs at the Small and Medium Enterprises Agency of Minahasa Regency is hindered by budget limitations. 3) The quality and quantity of human resources in the office are still inadequate. 4) Program administration targets have not reached the set targets and objectives. 5) There is a need for broader and unrestricted socialization for business actors.